Clustering, methodology, and mechanistic insights into acetate chemical ionization using high-resolution time-of-flight mass spectrometry - P. Brophy; D. K. Farmer (Atmospheric Measurement Techniques, 2016)
We present a comprehensive characterization of cluster control and transmission through the Tofwerk atmospheric pressure interface installed on various chemical ionization time-of-flight mass spectrometers using authentic standards. This characterization of the atmospheric pressure interface allows for a detailed investigation of the acetate chemical ionization mechanisms and the impact of controlling these mechanisms on sensitivity, selectivity, and mass spectral ambiguity with the aim of non-targeted analysis. Chemical ionization with acetate reagent ions is controlled by a distribution of reagent ion-neutral clusters that vary with relative humidity and the concentration of the acetic anhydride precursor. Deprotonated carboxylic acids are primarily detected only if sufficient declustering is employed inside the atmospheric pressure interface. The configuration of a high-resolution time-of-flight chemical ionization mass spectrometer (HR-TOF-CIMS) using an acetate chemical ionization source for non-targeted analysis is discussed. Recent approaches and studies characterizing acetate chemical ionization as it applies to the HR-TOF-CIMS are evaluated in light of the work presented herein.